1998
DOI: 10.1007/s001050050727
|View full text |Cite
|
Sign up to set email alerts
|

HIV-assoziierte Psoriasis

Abstract: Between 1982 and 1995, over 700 HIV-infected patients with different skin diseases were registered at the Department of Dermatology, Benjamin Franklin Medical Center, The Free University of Berlin. Thirty-six of them (approximately 5%) were diagnosed as having psoriasis. This is clearly a higher prevalence of psoriasis than in the general population (1-2%). If psoriasis lesions are not clinically seen before diagnosis of HIV infection, the disease will preferentially (approximately 80% of these cases) appear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…There has been debate in the literature on the prevalence of HIV-associated psoriasis (80). The largest study on this subject to date found no association when compared to the prevalence of psoriasis in the general population but other smaller studies have noted an increased rate of psoriasis in HIV patients (81)(82)(83).…”
Section: Inflammatory Conditions 21 Psoriasismentioning
confidence: 99%
“…There has been debate in the literature on the prevalence of HIV-associated psoriasis (80). The largest study on this subject to date found no association when compared to the prevalence of psoriasis in the general population but other smaller studies have noted an increased rate of psoriasis in HIV patients (81)(82)(83).…”
Section: Inflammatory Conditions 21 Psoriasismentioning
confidence: 99%
“…systemic immunosuppression [3]. A study in Berlin found that 36 of 700 HIV+ patients had psoriasis, with 80% of them being in late stages of HIV [4]. Their psoriasis course was severe, prolonged and had more frequent exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…La sévérité du psoriasis est corrélée au degré d'immunodépression : les lésions cutanées augmentent lorsque le taux de CD4 diminue, pouvant ainsi constituer un indice clinique de la progression de l'infection par le VIH (7,8,55,56). A l'inverse le psoriasis s'améliore lorsque l'infection par le VIH est bien contrôlée par les traitements antirétroviraux (5)…”
Section: B) Cliniqueunclassified